Empowering electricity consumers through demand response: Why and how - Mariana Weiss; Enrique Chueca; Jorge Jacob; Felipe Gonçalves; Marina Azevedo; Adriana Gouvêa; Pauline Ravillard; Michelle Hallack (Inter-American Development Bank (IDB), 2022)
Massive digitalization advances have made demand response (DR) programs feasible in the residential sector; however, most households in Latin America and the Caribbean (LAC) region do not know about these types of programs. In this report, the authors explore experiments about the willingness of residential consumers to adopt demand responses (DR) to reduce their bills. The authors analyze the likelihood of lower- and middle-income households across 11 LAC countries, adopting a DR plan. The questionaries counted on explanations about the purposes and benefits of the DR programs. The authors also analyzed the type of communication technology to which consumers are more likely to be responsive. Most interviewees understood that it would be fair to have peak and off-peak tariffs to cover supply costs. In three of the five cases analyzed, more than 50% of interviewees chose to move to a DR plan. Those were the case of the DR programs with a peak saving goal and pre-agreed discount, and heater or AC control by the utility during peak times. The results suggest that policymakers should start to consider demand response programs as a tool to increase the affordability of electricity services for residential consumers. It is important to consider the learning curve that will be required of users, services providers, and regulators.
Keywords: 330; Electricity; Consumer behavior; Electricity industry; Latin America; Caribbean region; Elektrizität; Konsumentenverhalten; Elektrizitätswirtschaft; Lateinamerika; Karibischer Raum